2011
DOI: 10.1063/1.3665700
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the upper critical field in codoped iron-arsenic high-temperature superconductors

Abstract: We present the first study of codoped iron-arsenide superconductors of the 122 family (Sr/Ba) 1−x K x Fe 2−y Co y As 2 with the purpose to increase the upper critical field H c2 compared to single doped Sr/BaFe 2 As 2 materials. H c2 was investigated by measuring the magnetoresistance in high pulsed magnetic fields up to 64 T. We find, that H c2 extrapolated to T = 0 is indeed enhanced significantly to ≈ 90 T for polycrystalline samples of Ba 0.55 K 0.45 Fe 1.95 Co 0.05 As 2 compared to ≈ 75 T for Ba 0.55 K 0.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…The magnetic field dependence of ρ ab (P , T ) for all studied single crystals around the OPD region is exemplified by the x = 0.11 sample in figure 2(d). The small suppression of the SC transition as a function of field up to 9 T is consistent with the high critical fields observed in these compounds [4][5][6][7][8][9][10][11][12][13]32]. Interestingly, the resistivity in the normal state of BaFe 1.89 Cu 0.11 As 2 shows a small positive magnetoresistance (MR) for all applied pressures (see figure 2(e)).…”
Section: Resultssupporting
confidence: 84%
“…The magnetic field dependence of ρ ab (P , T ) for all studied single crystals around the OPD region is exemplified by the x = 0.11 sample in figure 2(d). The small suppression of the SC transition as a function of field up to 9 T is consistent with the high critical fields observed in these compounds [4][5][6][7][8][9][10][11][12][13]32]. Interestingly, the resistivity in the normal state of BaFe 1.89 Cu 0.11 As 2 shows a small positive magnetoresistance (MR) for all applied pressures (see figure 2(e)).…”
Section: Resultssupporting
confidence: 84%
“…We note that the transition slightly broadens upon increasing the magnetic field. This is expected in a polycrystalline material possessing an anisotropic H c2 (T ) as anticipated for a quasi-two dimensional electronic structure [26]. The H c2 (T ) curves obtained from T onset c,ρ , T mid c,ρ , and T final c,ρ are displayed in…”
Section: Introductionmentioning
confidence: 62%
“…While pressure‐induced superconductivity in stoichiometric SrFe2As2 as well as superconductivity on electron‐ and hole‐doping has been studied extensively , only one combined pressure–hole‐doping study has been reported in Sr1xKxFe2As2 , but no pressure–electron‐doping investigation. Substituting Fe by Co in SrFe2xCoxAs2 corresponds to an electron doping directly inside the iron‐arsenide layers.…”
Section: Introductionmentioning
confidence: 99%
“…This is justified by the low residual resistivity ratio (as low as 4) [19], the low superconducting volume fraction (<20%) of the parent compound [10], and the tendency of pnictide superconductors to have a small l due to the low Fermi velocities [35] and high scattering rates [30,36]. A comparison of the mean free path as estimated 3 from published resistivity data [37], and the coherence length as calculated later in this paper, gives values for l that are less than ξ at all dopings, but of similar order of magnitude.…”
Section: Discussionmentioning
confidence: 99%